Polyelectrolyte complex micelles by self-assembly of polypeptide-based triblock copolymer for doxorubicin delivery - Jeong Hwan Kim; Thiruganesh Ramasamy; Tuan Hiep Tran; Ju Yeon Choi; Hyuk Jun Cho; Chul Soon Yong; Jong Oh Kim (Elsevier, 2014)
Polyelectrolyte complex micelles were prepared by self-assembly of polypeptide-based triblock copolymer as a new drug carrier for cancer chemotherapy. The triblock copolymer, poly(l-aspartic acid)-b-poly(ethylene glycol)-b-poly(l-aspartic acid) (PLD-b-PEG-b-PLD), spontaneously self-assembled with doxorubicin (DOX) via electrostatic interactions to form spherical micelles with a particle size of 60-80 nm (triblock ionomer complexes micelles, TBIC micelles). These micelles exhibited a high loading capacity of 70% (w/w) at a drug/polymer ratio of 0.5 at pH 7.0. They showed pH-responsive release patterns, with higher release at acidic pH than at physiological pH. Furthermore, DOX-loaded TBIC micelles exerted less cytotoxicity than free DOX in the A-549 human lung cancer cell line. Confocal microscopy in A-549 cells indicated that DOX-loaded TBIC micelles were transported into lysosomes via endocytosis. These micelles possessed favorable pharmacokinetic characteristics and showed sustained DOX release in rats. Overall, these findings indicate that PLD-b-PEG-b-PLD polypeptide micelles are a promising approach for anti-cancer drug delivery.